INTERSECTIONALITY OF CLASS AND VIOLENCE AGAINST CHILDREN IN PAKISTAN - Nasir Abbas; Syed Ali Abid Naqvi; Adil Zaman (International Journal of Contemporary Issues in Social Sciences, 2024)
This study has been designed to evaluate the intersectionality of class and violence against children in Pakistan. Violence against children has been fermenting but there is little literature available to explain the impacts of this new phenomenon on the lateral life of neglected children in Pakistan. This study has been conducted using a quantitative approach. The population consisted of children residing at four Child Protection Institutions (CPI) including Lahore, Gujranwala, Faisalabad, and Rawalpindi. A sample of 230 children has been selected using a classified random sampling technique. It is worth mentioning here that all the children are aged less than 18 years and rescued before 30 days. A cross-sectional survey has been conducted and a structured questionnaire has been constructed. It has been divided into different parts including socio-economic characteristics, violence, and health status. It has been pre-tested from 30 randomly selected children and the value of Alpha has ranged from .702 to .864. frequency distribution, descriptive statistics, correlation, and independent sample T-tests have been employed to draw results and conclusions. The study findings outlined that there was a significant correlation between physical, sexual, emotional, spiritual, and psychological violence social well-being, and physical and psychological health. Similarly, the statistical analysis shows that there is a significant difference in financial abuse between rural and urban background destitute and neglected children in the custody of the Child Protection & Welfare Bureau in Punjab.